127k views
1 vote
If y= 1-x+x²/1+x-x² than how about y'=?
This question is about derived function.

1 Answer

1 vote

Answer:

as


(d)/(dx)\left(1-x+(x^2)/(1)+x-x^2\right)=0

so


y'=0

Explanation:

Given the function


y=\:1-x+(x^2)/(1)+x-x^2

Taking derivative


(d)/(dx)\left(1-x+(x^2)/(1)+x-x^2\right)


\mathrm{Apply\:the\:Sum/Difference\:Rule}:\quad \left(f\pm g\right)'=f\:'\pm g'


=(d)/(dx)\left(1\right)-(d)/(dx)\left(x\right)+(d)/(dx)\left((x^2)/(1)\right)+(d)/(dx)\left(x\right)-(d)/(dx)\left(x^2\right)

as


(d)/(dx)\left(1\right)=0
\mathrm{Derivative\:of\:a\:constant}:\quad (d)/(dx)\left(a\right)=0


(d)/(dx)\left(x\right)=1
\mathrm{Apply\:the\:common\:derivative}:\quad (d)/(dx)\left(x\right)=1


(d)/(dx)\left((x^2)/(1)\right)=2x
\mathrm{Apply\:the\:Power\:Rule}:\quad (d)/(dx)\left(x^a\right)=a\cdot x^(a-1)


(d)/(dx)\left(x\right)=1
\mathrm{Apply\:the\:common\:derivative}:\quad (d)/(dx)\left(x\right)=1


(d)/(dx)\left((x^2)/(1)\right)=2x
\mathrm{Apply\:the\:Power\:Rule}:\quad (d)/(dx)\left(x^a\right)=a\cdot x^(a-1)

substituting all the values in the expression


=(d)/(dx)\left(1\right)-(d)/(dx)\left(x\right)+(d)/(dx)\left((x^2)/(1)\right)+(d)/(dx)\left(x\right)-(d)/(dx)\left(x^2\right)


=0-1+2x+1-2x


=0

Hence,


(d)/(dx)\left(1-x+(x^2)/(1)+x-x^2\right)=0

Therefore,


y'=0

User Franck Mesirard
by
5.7k points